A proposed clinical coagulation score for research in trauma-induced coagulopathy - Eitel, Andrew P; Moore, Ernest E; Sauaia, Angela; Kelher, Marguerite R; Vigneshwar, Navin G; Bartley, Matthew G; Hadley, Jamie B; Burlew, Clay C; Campion, Eric M; Fox, Charles J; Lawless, Ryan A; Pieracci, Frederic M; et al. (The journal of trauma and acute care surgery, 2023)
Trauma-induced coagulopathy (TIC) has been the subject of intense study for greater than a century, and it is associated with high morbidity and mortality. The Trans-Agency Consortium for Trauma-Induced Coagulopathy, funded by the National Health Heart, Lung and Blood Institute, was tasked with developing a clinical TIC score, distinguishing between injury-induced bleeding from persistent bleeding due to TIC. We hypothesized that the Trans-Agency Consortium for Trauma-Induced Coagulopathy clinical TIC score would correlate with laboratory measures of coagulation, transfusion requirements, and mortality. Trauma activation patients requiring a surgical procedure for hemostasis were scored in the operating room (OR) and in the first ICU day by the attending trauma surgeon. Conventional and viscoelastic (thrombelastography) coagulation assays, transfusion requirements, and mortality were correlated to the coagulation scores using the Cochran-Armitage trend test or linear regression for numerical variables. Increased OR TIC scores were significantly associated with abnormal conventional and viscoelastic measurements, including hyperfibrinolysis incidence, as well as with higher mortality and more frequent requirement for massive transfusion ( p < 0.0001 for all trends). Patients with OR TIC score greater than 3 were more than 31 times more likely to have an ICU TIC score greater than 3 (relative risk, 31.6; 95% confidence interval, 12.7-78.3; p < 0.0001). A clinically defined TIC score obtained in the OR reflected the requirement for massive transfusion and mortality in severely injured trauma patients and also correlated with abnormal coagulation assays. The OR TIC score should be validated in multicenter studies. Prognostic and Epidemiological; Level IV.